Effectiveness of Cooperative Learning Model on Mastering Ellipsis Topic of Japanese language on Japanese Literature Student at Udayana University - Dewi, Ni Ketut Lisna Martini (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana; Vol 28 No 2 (2021) : SeptemberDO - 10.24843/ling.2021.v28.i02.p08, 2021)
This research was entitled "Effectiveness of Cooperative Learning Model on Mastery of Japanese Language Ellipsis Topic on Japanese Literature Students at Udayana University." This study aimed to analyze the understanding and mastery of the fifth semester students of Nihon Gengogaku Nyumon's Japanese Literature Department at Udayana University in the pretest and posttest phases with cooperative learning methods. This research focused on the film ellipsis entitled The Boy and the Beast / Bakemono No Ko directed by Mamoru Hasoda. The theory in this study used a theoretical study proposed by Halliday and Hasan.This research was an experimental research that used qualitative and quantitative approaches. The research method used in this research was observation and test. Observations were made during the implementation of the treatment. In data analysis activities, this research used quantitative data analysis and qualitative data analysis. The results of this study indicate that there was an increase in the learning process using the cooperative learning method with the type TPS (Think Pairs Share). This could be seen from the results of the pretest and posttest which had increased although not significantly. The pretest percentage for verbal ellipsis from 42.5% increased by 18.5% to 61% for noun ellipsis from 48% increased by 15% to 63% and for clause ellipsis from 56.5% increased by 0.5% to 57%. Based on these results, it could be concluded that there is an increase in student abilities because of the treatment which was carried out for four face-to-face meetings which were carried out on a platform that had been determined by the campus.